An Analysis of the Difficulty Factors in Learning Arabic in Class VIII - Amal Husain Harahap; Zulfahmi Lubis (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to analyze the factors of difficulty in learning Arabic in class VIII students at the Al-Ikhwan Foundation in Kotapinang, North Sumatra, in the 2021/2022 academic year. The approach in this study uses a qualitative type with a descriptive analytical study method. The research was carried out in the second (even) semester of the 2021/2022 academic year, as of April to May 2022. The subjects of this research were the class VIII students of the Al-Ikhwan Kotapinang Foundation, totaling 27 students. The object of research is related to the factors of difficulty in learning Arabic experienced by students. Data was collected through interview, observation, and document studies. The results of this study indicate that almost all of the eighth grade students of the Al-Ikhwan Foundation in Kotapinang have difficulties in learning Arabic, this is motivated by internal and external factors. The internal factors include interest in learning Arabic, lack of concentration in student learning when the teacher delivers teaching materials, and intelligence (students' skills in receiving lessons). While external factors include general elementary school graduates and children's learning environment at home that is less supportive.